Public-private partnership in recycling: an evaluation of its climate change impact reduction benefits - Dunmade, Israel (International Journal of Engineering and Technology, 2019)
One of the global environmental concern today is the potential climate change of our economic activities. Appropriately addressing the concern require the collective effort of all the stakeholders. This study analyzed a case of public-private collaboration that facilitates paint recycling in Alberta and the attendant climate change impact reduction benefits. The study approach involved literature search, conversation with partners, and lifecycle analysis of data collected from a corporate organization involved in the partnership. Results from the study showed that the paint recycling partnership provides a net monthly environmental benefit of reducing the potential climate change impact by 8,841.11 kg CO2-eq. It also resulted in the diversion of about 25% of paint containers and plastics from the landfills. The public private partnership in recycling provided synergetic economic and environmental benefits for the participating municipalities and the corporate organization involved in the project.